Authoritarianism and Constitutional Politics in Post-Authoritarian Indonesian Society: Reemergence or Legacy - Shimada, Yuzuru (Faculty of Law, Universitas Brawijaya, 2022)
This paper discusses how the legacy of authoritarianism in Indonesia has influenced the country’s post-authoritarian constitutional politics. Because of some degree of ideological continuity from the authoritarian period, post-authoritarian Indonesia shows a unique situation of constitutional politics. Specifically, the positioning of Pancasila as an incontestable state ideology exposes the freedom of expression and association to severe risks, even in post-authoritarian Indonesia. In the discussion of post-authoritarian Indonesian society and constitutional politics, I review how the violation of Pancasila has been defined in Indonesia both during and after the authoritarian period. To explore this issue, I examine the court judgments concerning the anti-subversion law in which anti-Pancasila activities were defined to restrict opinions. I then review the social organization law amended in 2017 to argue how the law links Pancasila with the discourse of Asian values. In conclusion, this paper argues that both during and after the authoritarian period, the interpretation of Pancasila was restricted, thus subjecting Indonesia’s political freedom to risk.